Strategy Of The Gemaharjo Village Government In Maintaining The Existence Of Independent Villages From 2020 To 2025 In Pacitan Regency - Larasati Kansa Widya Putri; Ekapti Wahjuni Djuwitaningsih (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the strategy of the Gemaharjo Village government in maintaining the existence of an independent village from 2020 to 2025 in Pacitan Regency. The study discusses the transformation of Gemaharjo Village into an independent village, the flagship programs of the independent village, the implantation of government strategies in sustaining village independence, and the government’s efforts to maintain the existence of the independent village. This research employs a qualitative approach to explore and gain an in-depth understanding of data from a group of individuals. Data were collected trough in-depth interviews, data analysis, and documentacion. The sampling technique used was purposive sampling, selecting informants in this study consisted of the Head of Gemaharjo Village, the Village Secretary, and the Head of Village Planning Affairs. The result indicate that Gemaharjo Village has successfully achieved and maintained its status as an independent village through the fulfillment of the Developing Village Index (Indeks Desa Membangun/IDM) indicators, supported by adequated village facilities and the strengthening of economic, educational, health, agricultural, and livestock sectors. This independence is further reinforced by the development of leading sectors based on local potential, particulary dairy cattle farming through collaboration with Nestlé as well as the innovation of local products such as Raja Subali, which serves as the village’s distinctive identity. The success of Gemaharjo Village is also supported by intregrated village government startegies, policy consistency, accountable governance, and active community participation, enabling the sustainability of development and the long-term maintenance of village independence.